Relationships Between Biological Heavy Metals and Breast Cancer: A Systematic Review and Meta-Analysis - Liu, Lin; Chen, Jie; Liu, Chang; Luo, Yuxuan; Chen, Jiayun; Fu, Yuanyuan; Xu, Yajie; Wu, Haili; Li, Xue; Wang, Hui (Frontiers in Nutrition, 2022)
Introduction Heavy metals were classified as essential, probably essential and potentially toxic in the general population. However, the categories are still not clear for the patients with breast cancer (BC). Until now, it has been reported inconsistently on the effect of heavy metals in BC. In this meta-analysis, we aimed to assess the effect of heavy metals on BC, and review the potential mechanisms systematically. Methods We searched for epidemiological studies about the effect of heavy metals on BC in English published before Sep 2020 in PubMed, Web of Science and Embase databases. 36 studies in total, comprising 4151 individuals came from five continents around the world, were identified and included. Results In all biological specimens, Cu, Cd and Pb concentration was higher, but Zn and Mn concentration was lower in patients with BC than in non-BC participants. Specifically, elevated plasma / serum Cu and Cd, as well as decreased Zn and Mn, were found in cases; in hair, only lower Zn was observed. Further, the status of trace elements probably needs to be re-explored, particularly in BC. More prospective studies, randomized clinical trials and specific pathogenic studies are needed to prevent BC. The main mechanisms underlying above-mentioned findings are comprehensively reviewed. Conclusion For BC, this review included all the epidemiological studies to identify the current knowledge gaps which we currently have in understanding the impact of different heavy metals on BC.